Moral Hazard, Agency Costs, and Asset Prices in a Competitive Equilibrium - Ramakrishnan, Ram T. S.; Thakor, Anjan V. (Journal of Financial and Quantitative Analysis, 1982)
Ram T. S. Ramakrishnan, Anjan V. Thakor, Moral Hazard, Agency Costs, and Asset Prices in a Competitive Equilibrium, The Journal of Financial and Quantitative Analysis, Vol. 17, No. 4, Proceedings of the 17th Annual Conference of the Western Finance Association, June 16-19, 1982, Portland, Oregon (Nov., 1982), pp. 503-532